The role and mechanisms of macrophages in chronic pain: A peripheral-to-central perspective - Jiao Liu; Yeru Chen; Gang Chen (Brain Research Bulletin, 2025)
Chronic pain is a worldwide health concern that profoundly impacts patients' quality of life and imposes a substantial economic burden on society. The development is influenced by intricate physiological mechanisms, notably the sensitization of peripheral nociceptors and central sensitization. Macrophages, essential immune cells, are pivotal in the onset and maintenance of chronic pain. This article analyzes the functions of macrophages in peripheral nociceptors, dorsal root ganglia (DRG), and the central nervous system (CNS), particularly in the spinal dorsal horn and brain. Research indicates that peripheral macrophages elevate nociceptor sensitivity via the release of pro-inflammatory cytokines, such as TNF-α, IL-1β, IL-6, and PGE₂; in the DRG, macrophages amplify pain signaling by influencing neuronal excitability; within the (CNS), microglia and border-associated macrophages (BAM) perform unique functions in neuroinflammation and pain perception. Microglia enhance pain perception by facilitating central sensitization, whereas BAMs, located at the borders of the central nervous system, participate in neurovascular connections, immune control, and associated mechanisms. Despite considerable advancements, the precise functional roles of macrophages across many anatomical locations remain inadequately investigated and lack systematic comparison. Future study ought to concentrate on the geographically different processes of macrophages, specifically employing single-cell transcriptomics and other modern technologies to elucidate macrophage heterogeneity and its intricate role in chronic pain. An enhanced comprehension of these pathways may facilitate novel approaches for macrophage-targeted treatments in chronic pain management.